Biobank Report: United Kingdom. Issue 1 (2016) - Kaye, Jane; Bell, Jessica; Briceno, Linda; Mitchell, Colin
Abstract : The United Kingdom is a leader in genomics research, and the presence of numerous types of biobanks and the linking of health data and research within the UK evidences the importance of biobank-based research in the UK. There is no biobank-specific law in the UK and research on biobank materials is governed by a confusing set of statutory law, common law, regulations, and guidance documents. Several layers of applicable law, from European to local, further complicate an understanding of privacy protections. Finally, biobanks frequently contain data in addition to the samples; the legal framework in the UK generally differentiates between data and samples and the form of the data affects the applicability of legal provisions. Biobanks must be licensed by the Human Tissue Authority; certain projects must be reviewed by Research Ethics Committees, and all projects are encouraged to be reviewed by them. Data Access Committees in biobanks are also common in the UK. While this confusing array of legal provisions leaves privacy protections in biobanking somewhat unclear, changes at the EU level may contribute to harmonization of approaches to privacy.